Validação de guia para consulta de enfermagem a adultos com diabetes mellitus tipo 2 - Bedin, Bárbara Belmonte (2023)
INTRODUCTION: the nursing consultation for adults with Diabetes Mellitus is an appropriate space for the development of educational techniques with a comprehensive approach in the pursuit of promoting and valuing self-care. In order to systematize care during the nursing consultation, the use of technologies is essential, as they help to promote greater security for professionals and users, improve decision-making, broaden the nurse's view of the health-disease process in the context of primary care, qualifying care. GENERAL OBJECTIVE: to validate the nursing consultation guide for adults with type 2 Diabetes Mellitus in Primary Health Care. METHOD: methodological study, with a quantitative approach, contemplating the validation stage of the guide for the nursing consultation for adults with Type 2 Diabetes Mellitus, together with expert judges in the area ofnursing and the target audience regarding the content and appearance of the guide, which occurred by agreement between them. The study participants were the expert judges in the field of nursing and the target audience consisted of nurses. A Likert scale instrument was used for validation. Data collection took place from December 2022 to March 2023, online and in person. After double typing of the data was performed, they were stored in a Microsoft Office Excel spreadsheet and analyzed using the Statistical Package for the Social Sciences program, based on descriptive statistical analysis, with simple frequency distribution, and the index was calculated. Content Validity. The study complies with ethical precepts in accordance with Resolutions 466/2012 and 510/2016. RESULTS: the Guide needed to be validated in two evaluation rounds, reaching a CVI greater than or equal to 0.80% in all items evaluated by both the expert judges and the target audience. In the second round, according to the evaluation of the expert judges, in relation to the content and objective, the items referring to the information being scientifically correct and structured, the amount of content, whether the objective of the nursing consultation is completed, whether the Guide is appropriate, has necessary topics, is presented in an understandable, adequate and objective way, there is a logical sequence, and if it is practical to be used in the nursing consultation of adults with Type 2 Diabetes Mellitus, who received CVI 1. In front of the structure and design, all items reached CVI 1. In the evaluation of the target audience, all evaluated items received CVI 1. Also, suggestions for improvements to the Guide were proposed, which were accepted and changed to the final version of the material. FINAL CONSIDERATIONS: the Guide was validated in terms of appearance and content, and can be considered a material suitable for use by nurses in Primary Health Care. It can be used when conducting nursing consultations with users with Type 2 Diabetes Mellitus.